2023
DOI: 10.1590/1519-6984.246333
|View full text |Cite|
|
Sign up to set email alerts
|

Partial replacement of fish meal with Moringa oleifera leaf meal in practical diets of Cirrhinus mrigala fingerlings

Abstract: Fish protein is serving as a source of nutrition for protein starving world. However, sustainable aquaculture products require inexpensive plant by-products due to finite sources of fish meal. Therefore, this study was conducted to examine nutrient utilization, growth performance and hematological indices of Cirrhinus mrigala fingerlings fed on Moringa oleifera leaf meal (MOLM) based diets. Fish were fed with six isonitrogenous and isoenergetic diets having MOLM as a substitute of fish meal (FM) at the levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The results of the present study are congruent with those of other researchers who have suggested that fish meal can partially be replaced with aquatic macrophytes [8,[44][45][46][47][48][49]. The results of the growth characteristics and feed consumption of C. carpio var.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study are congruent with those of other researchers who have suggested that fish meal can partially be replaced with aquatic macrophytes [8,[44][45][46][47][48][49]. The results of the growth characteristics and feed consumption of C. carpio var.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in agreement with Nsofor et al (2012) [14] who says fish fed with Moringa Leaf Meal (MLM) in replacement of fishmeal at 60% inclusion rate resulted in the lowest growth response due to the low palatability of the diets which may lead to poor feed intake. However, Tabassum et al (2021) [13] reported that partial replacement of fishmeal with Moringa oleifera Leaf Meal (MOLM) was not effective beyond 10% inclusion levels in terms of growth performance and nutrient utilization. The highest weight gain was achieved in 3% MAD based diet, followed by 3% MHD and 3% MED based diets respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary preparations from MO were included in many animal diets such as chicken [113], fshes [114,115], sheep [116], cows [117], and rabbits [118]. For chicken, Moringa diets formulated from leaves and stems improved the growth performance and carcass trait [119], and productivity and the quality of egg production [120].…”
Section: Moringa Oleifera As a Source For Animal Dietsmentioning
confidence: 99%